The Bosworth Psalter: A critical edition. - Makothakat, John M. (University of Ottawa (Canada), 1972)
This dissertation is an edition of the psalms, together with their partial interlinear Old English gloss and Latin commentary, contained in folios 4r--95v of the British Museum Manuscript, Additional 37517, known as the Bosworth Psalter. The psalter in full (psalms 1--151) and the Latin commentary (titular, interlinear and marginal commentaries on psalms 1--39. 1--7; titular commentary on psalms 40--50; titular, interlinear and marginal commentaries on psalms 71--83: 1--3) are being edited here for the first time. The only material previously edited appearing here is the twenty-nine psalms with their interlinear Old English gloss (40: 5, 50: 6--21, 53, 63, 66, 68--70, 85, 101, 118--133, 139: 2, 9, 140: 1--4, 142), edited by Uno Lindelof, in 1909; these are being included in this edition, as it aims at providing a complete text of the psalms. This edition was prepared from microfilm and photostatic copies of the manuscript, and checked, letter by letter, against the original. The text is presented unemended, even the obvious scribal errors being retained but recorded and corrected in the notes. The text is arranged in three separate parts and is preceded by an Introduction. The Introduction deals with the description of the manuscript, its contents, its date and provenance, its general characteristics, and its particular features as a Benedictine Prayer Book. It discusses, very briefly, the history of the Roman and Gallican versions of the psalms, the tradition of Old English gloss in the psalters, and the evolution of exegetical commentary on the psalms. Under these headings, the main features of the psalms, gloss, and commentary in the Bosworth Psalter are examined. The Introduction also explains the textual procedure adopted in this edition. The first part (pages 1--238) contains the psalms and the interlinear Old English gloss. The version of the psalms in the Bosworth Psalter is Roman, but altered in some places, to fit the commentary, which is based on a Gallican version. As the text of the Bosworth Psalter is that of the Roman version, every effort has been made in this edition to perceive and render the original Roman version of the manuscript. Notes to the first part are strictly textual, recording the alterations from the Roman to the Gallican, as well as other alterations, scribal errors, erasures, deletions, illegibility, and manuscript damage affecting the text. Lindelof's readings are noted, wherever this edition differs with his. A collation of the significant variant readings of the Latin text in the six extant Old English psalters and in the Benedictine critical edition of the roman Psalter is also given. The second and third parts (pages 239--630, and 631--923) contain the Latin commentary on psalms 1--50, and 71--83, respectively. To facilitate the reading of the commentary, the text of these psalms is repeated. Every attempt has been made to match each section of the commentary with its appropriate lemma and verse. In addition to textual notes, the second and third parts have referential notes. The Latin commentary is rich in biblical quotations, allusions, and echoes, most of which have been identified and recorded. Sources acknowledged by the commentator are traced from available editions. This dissertation has aimed at making an accurate text readily accessible, so that textual, linguistic, and source studies may be more easily pursued.
Keywords: Religion, Biblical Studies.